PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING: Studi Meningkatkan Hasil Belajar Sosiologi Siswa Kelas X IPS 1 di SMA Negeri 1 Depok-Sleman - Nugroho, Dwi; Nurrita, Teni (Asosiasi Dosen PTKIS Indonesia, 2024)
Sociology as a science has the object of research on social behavior, namely human behavior and social institutions. The purpose of this study is to determine the application of the Project Based Learning learning model and the learning outcomes of Sociology students in grade X Social Studies 1 SMA Negeri 1 Depok in 2022/2023. The study was conducted using the Classroom Action Research (PTK) method in 2 cycles. Each cycle consists of planning, execution, observation and reflection. The subject of this study was a student of Class X Social Studies 1 SMA Negeri 1 Depok. The results showed: first, the Project Based Learning learning syntax was carried out entirely. Second, the learning outcomes of students with the achievement of a KKM score of 75 in cognitive aspects increased after using the project-based learning learning model, namely obtaining completeness of 63.8% in cycle I to 88.8% in cycle II. Third, the average value of student learning outcomes in cyclone 1 of 70.28 increased in cycle II of 88.8. Fourth, the Project Based Learning learning model can be applied by teachers to Sociology subjects because it improves student learning outcomes. Based on the results of research and data analysis carried out, it can be concluded that the application of the project-based learning model can improve the learning outcomes of grade X IPS 1 students at SMA 1 Depok for sociology subjects with material on the function of sociology to recognize social symptoms in society for the 2022/2023 school year.